Collective action and youth: territorialities of youth collectives in the city of Governador Valadares-MG, Brazil - Maurer, Michele Silva; Vilarino, Maria Terezinha Bretas (Geografares, 2021)
This study aims to understand the multiple territorialities present in the context of youth groups and the relationships that produce them. The study on youth focuses on collective action associations and the relationships that young people establish with the city of Governador Valadares in Minas Gerais, Brazil, occupying space and producing territorialities. Youth collectives connect young people, promote sociability and enable mediation with the lived reality, creating and modifying relations with the urban space. By the notion of youth groups, it is understood that these are organized by young people and that they emerge from present situations, however, the organization model is not exclusive to youth, but corresponds to a trend of associativism today, as it presents more flexible structures, as well as more horizontal organizational and management dynamics.